Tiga Komponen Utama (Sumber Daya Manusia, Sistem Kerambah, Sistem Pengelolaan) Pemberdayaan Embung Cokro, Sukoanyar, Pakis, Malang - Nafisa Qotrul Hidayah; Faizah Fajar Putri; Nur Muhammad Taqiyyuddin Subki; Hermawan Wibawa Putra; Binti Nur 'Alimah (Es-Syajar:Journal of Islam, Science and Technology Integration, 2023)
Kuliah Kerja Mahasiswa (KKM) is a forum and a concrete manifestation of student obligations in carrying out the Tri Dharma of Higher Education in the field of community service. The KKM service activity for group 33 of the State Islamic University of Maulana Malik Ibrahim Malang was carried out in Cokro Hamlet, Sukoanyar Village, Pakis District, Malang Regency. Community service is carried out in various aspects, one of which is empowering village resources. Sukoanyar Village has a reservoir or irrigation pond which is a village asset. However, the reality on the ground is that the Cokro Reservoir has experienced several setbacks, namely its less productive activities and management. The purpose of implementing embung empowerment socialization is as an effort to achieve the main goal, namely cokro embung which is productive both in terms of empowerment value, economic value, aesthetic value and profit value. The effort of the KKM 33 UIN Malang group in assisting this empowerment process was to socialize the empowerment of cokro ponds. The content of the socialization is about the main components of the reservoir management which include; productivity of human resources, cage systems, harvesting systems, feed systems and suitable types of fish. Fish that are suitable for cultivation are tilapia. Apart from that, KKM-33 of UIN Malang has also built a garden on the side of the pond and carried out stocking of fish ready for fishing in order to help the process of empowering the pond.